(untitled) (Almanack, 2020)
Violence was an important part of the nation building process in Argentina during the 19th century. From the wars of independence to the confrontations that erupted within and between the new nations, armed confrontations were frequent and played a key role in the new polity. Traditionally, Argentine historiography has considered uprisings to be disruptive actions that hampered the institutionalization of the political system outlined in the Constitution. Historians understood these forms of political mobilization as a part of minor power struggles between elites who through their behavior, perpetuated political instability and delayed state consolidation. Recent empirical local studies offer a different view of political violence in Argentina during state formation. This article reviews those studies and puts forward a guideline for a new global interpretation of the concept and practice of violence between national unification (1862) and the consolidation of the state (1880).